A freshwater fish defies ancient mountain ranges and drainage divides: extrinsic and intrinsic influences on the evolutionary history of a recently identified galaxiid. (11th April 2013) - Chakona, Albert; Swartz, Ernst R.; Gouws, Gavin; Bloomer, Paulette; Riddle, Brett
Abstract Aim A river hierarchy model has been proposed for stream‐dwelling taxa, where genetic structure is expected to reflect geographical proximity and connectivity of river systems. However, many exceptions and deviations from this model have been detected. The present study tested three biogeographical hypotheses (River Hierarchy, Palaeoriver Systems and Interdrainage Dispersal) to assess how a recently identified galaxiid, Galaxias sp. 'nebula', came to have a wide distribution across multiple currently isolated river systems in the Cape Floristic Region of South Africa. Location Seventeen river systems in the Cape Floristic Region at the southern tip of Africa. Methods We analysed mitochondrial cytochrome c oxidase subunit I and cytochrome b sequences from across the entire distribution of Galaxias sp. 'nebula' and compared divergence times between populations with known geological and climatic events to explain the observed geographical patterns of genetic diversity. Results The data revealed historical divergence between the Olifants, Berg and southward‐draining river systems. The phylogeographical analyses revealed that range expansion occurred across currently isolated river systems, with some haplotypes being shared between geographically distant river systems. Molecular dating revealed recent divergence times between populations from isolated river systems (c. 4000–1, 200, 000 years ago). Main conclusions The phylogeographical pattern of Galaxias sp. 'nebula' indicates that drainage basin boundaries have historically not played a dominant long‐term role in structuring this lineage. River captures are not widespread and frequent enough to explain the observed genetic patterns. Galaxias sp. 'nebula' has been able to disperse between proposed palaeoriver systems. Interdrainage dispersal via episodic freshwater connections during periods of increased rainfall during the Pleistocene and Holocene epochs seems to have played an important role in allowing this lineage to attain and maintain its wide contemporary distribution.